A DESA CINANJUNG DAN KETERSEDIAAN POTENSI ALAM DALAM KEGIATAN BAZAR GANTOENG - Yenita Sandra Sari; Anggarana Anggarana; Aji Arief; Dita Aulia; Maslan Mahmud; Feriyanto Ramadhan; Ari Putra Nugraha; Nurmawan N Tela; Mardiansyah Mardiansyah; Sahrin Zainudin Luna; Sani Abdul Rahman (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2021)
As a form of community service, in 2020 the thematic Real Work Lecture (KKN) will be carried out in the conditions of the Covid-19 pandemic. The expected goal is to gain learning experiences through community development activities that are concrete for the benefit of students and the community where they are placed and to realize the link between the academic world and the community. The purpose of carrying out this activity is to realize ideas, or ideas in innovation by taking into account the local potential to be empowered, as an effort to prevent the spread of Covid-19 and to provide assistance in the form of realizing natural beauty that can be enjoyed by the wider community. In this activity, it is carried out by observing, interviewing, and participating in mingling in the lives of the community by implementing health protocols in each activity. The results obtained are the completion of the idea, design, and realization of the Bazar Gantoeng destination so that residents can enjoy the beauty of nature and create a place for natural tourism, beneficial to the community.